Bariatric Surgery and Gut-Brain-Axis Driven Alterations in Cognition and Inflammation - Custers E; Franco A; Kiliaan AJ (Dove Medical Press, 2023)
Emma Custers,* Ayla Franco,* Amanda Johanne Kiliaan Department of Medical Imaging, Anatomy, Radboud University Medical Center, Donders Institute for Brain Cognition and Behaviour, Nijmegen, the Netherlands*These authors contributed equally to this workCorrespondence: Amanda Johanne Kiliaan, Department of Medical Imaging, Anatomy, Preclinical Imaging Centre, Radboud Alzheimer Center, Radboud University Medical Center, Donders Institute for Brain, Cognition and Behaviour, Geert Grooteplein 21N, Nijmegen, 6525 EZ, the Netherlands, Tel +31 24 3614378, Email Amanda.Kiliaan@Radboudumc.nlAbstract: Obesity is associated with systemic inflammation, comorbidities like diabetes, cardiovascular disease and several cancers, cognitive decline and structural and functional brain changes. To treat, or potentially prevent these related comorbidities, individuals with obesity must achieve long-term sustainable weight loss. Often life style interventions, such as dieting and increased physical activity are not successful in achieving long-term weight loss. Meanwhile bariatric surgery has emerged as a safe and effective procedure to treat obesity. Bariatric surgery causes changes in physiological processes, but it is still not fully understood which exact mechanisms are involved. The successful weight loss after bariatric surgery might depend on changes in various energy regulating hormones, such as ghrelin, glucagon-like peptide-1 and peptide YY. Moreover, changes in microbiota composition and white adipose tissue functionality might play a role. Here, we review the effect of obesity on neuroendocrine effects, microbiota composition and adipose tissue and how these may affect inflammation, brain structure and cognition. Finally, we will discuss how these obesity-related changes may improve after bariatric surgery.Keywords: obesity, cognitive impairment, inflammation, gut hormones, adipose tissue, bariatric surgery